Selectively Emotional: How Smartphone Use Changes User-Generated Content - Melumad, Shiri; Inman, J. Jeffrey; Pham, Michel Tuan (Journal of Marketing Research, 2019)
User-generated content has become ubiquitous and very influential in the marketplace. Increasingly, this content is generated on smartphones rather than personal computers (PCs). This article argues that because of its physically constrained nature, smartphone (vs. PC) use leads consumers to generate briefer content, which encourages them to focus on the overall gist of their experiences. This focus on gist, in turn, tends to manifest as reviews that emphasize the emotional aspects of an experience in lieu of more specific details. Across five studies—two field studies and three controlled experiments—the authors use natural language processing tools and human assessments to analyze the linguistic characteristics of user-generated content. The findings support the thesis that smartphone use results in the creation of content that is less specific and privileges affect—especially positive affect—relative to PC-generated content. The findings also show that differences in emotional content are driven by the tendency to generate briefer content on smartphones rather than user self-selection, differences in topical content, or timing of writing. Implications for research and practice are discussed.